Investigation of some biologic activities of Swertia longifolia Boiss - Hajimehdipoor, H. (Medknow Publications & Media Pvt Ltd, 2013)
Swertia species are widespread in Eastern and Southern Asian countries and used in traditional medicine as anti-pyretic, analgesic, gastro and liver tonic. Among different species, only Swertia longifolia grows in Iran. In this investigation, antioxidant, cytotoxic and acetylcholinesterase inhibitory activities of S. longifolia have been studied. Aerial parts and roots of the plant were collected, dried and extracted with methanol 80% (total extract). Different extracts of the plant were obtained using hexane, chloroform, ethyl acetate, methanol, methanol:water (1:1) and water, respectively. Cytotoxic activity was determined by MTT assay on MDBK, HepG2, MCF7, HT29 and A549 cell lines. Antioxidant activity was measured by 2,2-diphenyl-1-picryl hydrazyl (DPPH) free radicals and acetylcholinesterase inhibitory (AChEI) effect was evaluated based on Ellman’s method in 96-well microplates.The results showed no cytotoxicity of the plant extracts on MDBK, HepG2, MCF7, HT29 and A549 cell lines up to 100 μg/ml. All samples showed radical scavenging activity but methanol extract of aerial parts and ethyl acetate extract of the roots showed the highest effects.Total extract of the roots showed higher AChEI activity than the aerial parts. Among different extracts, chloroform and ethyl acetate extracts of the roots and chloroform and methanol:water extracts of the aerial parts were more potent in AChEI assay. It is concluded that aerial parts and roots of the plant are rich in antioxidant agents with no cytotoxicity on selected cell lines up to 100 μg/ml. Moreover, since antioxidant and AChEI activity of compounds play an important role in the treatment of Alzheimer’s disorder, this plant might be a potential candidate for isolation of antioxidant and AChEI compounds which could be used as supportive treatment of Alzheimer’s disease.